Inside Back Cover: Porous Carbon Fibers Containing Pores with Sizes Controlled at the Ångstrom Level by the Cavity Size of Pillar[6]arene (Angew. Chem. Int. Ed. 22/2015). Issue 22 (29th April 2015) - Ogoshi, Tomoki; Yoshikoshi, Kumiko; Sueto, Ryuta; Nishihara, Hirotomo; Yamagishi, Tada‐aki
<x xml:space="preserve">Abstract</x> Controlling pore size at the Ångstrom level is very difficult, and requires inorganic templates that have to be removed. In their Communication on page 6466 ff., T. Ogoshi and co‐workers introduce a new method to synthesize porous carbon fibers without inorganic templates. Carbonization of the fibrous 2D porous sheets formed from hexagonal pillar[6]arenes gives porous carbon fibers with pores of a size precisely controlled at the Ångstrom level.